An Assessment of Uprising against the Indian Revolt of 1857: British Historiography: A Critical Analysis of the Indian Uprising against British Rule in 1857 (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Uprising of 1857 was in many ways a representation of such feelings among the people. The Uprising shook the foundation of British rule but was suppressed with great power and ruthlessness. The Uprising of 1857 is a great landmark in the history of India. The year 1857 symbolizes a turning point in the history of modern India because in that eventful year an upsurge, invariably referred to as the 'Mutiny' in most contemporary accounts, took on the dimensions of a rebellion as the princes and people of India, following the lead given by the sepoys, challenged a well -established administrative set up. Over the years, the nature and scope of this great struggle has been the subject of controversy with historians in India and overseas. During the last one and half century a massive literature have been produced by the historians and scholars on this event. However, it goes without saying that this Uprising occupies a unique peace in the annals of Indian freedom struggle.